Intrahepatic cholangiocarcinoma detected on 18F-PSMA-1007 PET/MR imaging in a prostate cancer patient: a case report and literature review - Sun, Yu; Wang, Haiyan; Yang, Yihong; You, Zhiwen; Zhao, Jun (Frontiers in Oncology, 2024)
Radionuclide probes-targeted prostate-specific membrane antigen (PSMA) is used in diagnosis and treatment of prostate cancer (PCa). Recent studies have shown that PSMA is expressed in the tumor neovascular endothelium, such as in malignant liver tumors(1-4). We report a case of PCa with incidental intrahepatic cholangiocarcinoma (ICC) detection using 18 F-PSMA-1007 and 18 Ffluorodeoxyglucose (FDG) positron emission topography (PET)/MRI . 18 F-PSMA-1007 PET/MRI of our patient with PCa showed that one liver lesion had high PSMA uptake. 18 F-FDG PET/MRI revealed minimal FDG uptake in the liver lesion. Histopathological examination revealed that the liver lesion was moderately to poorly differentiated cholangiocarcinoma. Our studies, along with others, demonstrated that malignant liver tumors, such as ICC, hepatocellular carcinoma (HCC), and combined hepatocellular-cholangiocarcinoma (CHC), and benign lesions, such as benign liver hemangioma, focal nodular hyperplasia, focal inflammation and steatosis, vascular malformation, and fatty sparing, exhibited elevated PSMA uptake. Moreover, PSMA-PET was superior to FDG-PET in detecting ICC and HCC, indicating that PSMA-PET may be used as alternative staging and to identify patients for PSMA-targeted therapy.